THE NORMATIVE RESPONSE TO PROBLEMS OF DETECTION AND INVESTIGATION OF CYBER CRIME - Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Certain aspects of cyber crime represent the essence of the problems that authorities prosecuting crimes committed by abuse of information technology face everyday. ﻿All these specific feauters of cyber crime crime must be taken into consideration in order to understand and overcome difficulties in investigation and prosecution of crimes and trial of perpetrators. Given all the above and in order to respond to the specific nature of criminal activities committed using computer networks and systems, it is understandable that countries strive to adapt or complement the existing criminal law provisions. ﻿ To create an appropriate legal framework for fighting this type of crime by means of criminal law, rules of substantive criminal law should incriminate certain behaviors and predict offenses against the confidentiality, integrity and availability of computer data and computer systemsand rules of criminal procedure law should determine the appropriate powers of the authorities in order to identify sources of illicit actions and collect information on the committed offense and the offender which could be used as evidence in criminal proceedings.